2013
DOI: 10.1016/j.jinorgbio.2013.05.011
|View full text |Cite
|
Sign up to set email alerts
|

The influence of R substituents in triphenylphosphinegold(I) carbonimidothioates, Ph3PAu[SC(OR)=NPh] (R=Me, Et and iPr), upon in vitro cytotoxicity against the HT-29 colon cancer cell line and upon apoptotic pathways

Abstract: The Ph3PAu[SC(OR)=NPh], R=Me (1), Et (2) and iPr (3), compounds are significantly cytotoxic to the HT-29 cancer cell line with 1 being the most active. Based on human apoptosis PCR-array analysis, caspase activities, DNA fragmentation, cell apoptotic assays, intracellular reactive oxygen species (ROS) measurements and human topoisomerase I inhibition, induction of apoptosis is demonstrated and both the extrinsic and intrinsic pathways of apoptosis have been shown to occur. Compound 1 activates the p73 gene, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 110 publications
1
19
0
Order By: Relevance
“…Specifically, it was demonstrated that 1 activates the p73 gene in contrast to each of 2 and 3 which activate the p53 gene. Further, an additional apoptotic mechanism was induced by 2, namely via the JNK/MAP pathway [22]. Given these promising early results, the present work continues an investigation of 1-3 by delving more deeply into cell apoptosis, release of cytochrome c, cell invasion, cell cycle analysis, gene expression, and in vivo toxicity assessment during zebrafish development.…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…Specifically, it was demonstrated that 1 activates the p73 gene in contrast to each of 2 and 3 which activate the p53 gene. Further, an additional apoptotic mechanism was induced by 2, namely via the JNK/MAP pathway [22]. Given these promising early results, the present work continues an investigation of 1-3 by delving more deeply into cell apoptosis, release of cytochrome c, cell invasion, cell cycle analysis, gene expression, and in vivo toxicity assessment during zebrafish development.…”
Section: Introductionmentioning
confidence: 74%
“…The thiocarbamides and triphenylphosphanegold(I) complexes were prepared as described previously [22].…”
Section: Synthesismentioning
confidence: 99%
See 3 more Smart Citations